A [SU(6)]4xZ_4 flavor model without mirror fermions (1994)
ABSTRACT: We introduce a three family extension of the Pati-Salam model which is anomaly free and contains in a single irreducible representation the known quarks and leptons without mirror fermions. Assuming that the breaking of the symmetry admits the implementation of the survival hypothesis, we calculate the mass scales using the renormalization group equation. Finally we show that the proton remains perturbatively stable.